Answer:
Explanation:
Given the functions g(x) = x − 3x and h(x) = 5x + 2, we are to calculatae for the expression;
a) (g - h)(x) an (g * h)(x)
(g - h)(x) = g(x) - h(x)
(g - h)(x) = x − 3x -(5x+2)
(g-h)(x) = x-3x-5x-2
(g-h)(x) =-7x-2
b) (g * h)(x) = g(x) * h(x)
(g * h)(x) = (x − 3x )(5x+2)
(g * h)(x) = 5x²+2x-15x²-6x
(g * h)(x) = 5x²-15x²+2x-6x
(g * h)(x) = -10x²-4x
c) To get (g + h)(−2), we need to first calculate (g + h)(x) as shown;
(g + h)(x) an (g * h)(x)
(g + h)(x) = g(x) +h(x)
(g + h)(x) = x − 3x + (5x+2)
(g+h)(x) = x-3x+5x+2
(g+h)(x) =3x+2
Substituting x = -2 into the resulting function;
(g+h)(-2) = 3(-2)+2
(g+h)(-2) = -6+2
(g+h)(-2) = -4